The role of nurses in smoking cessation interventions for patients: a scoping review - Yueying Jiang; Yuan Zhao; Panpan Tang; Xueqing Wang; Yunyu Guo; Leiwen Tang (BMC, 2024)
Abstract Background Smoking is a significant global public health concern, presenting substantial risks to individuals' health. Smoking cessation is essential for improving patients' well-being, and nurses play a critical role in assisting patients to quit smoking. However, there is a lack of research on nurses' specialized roles in smoking cessation interventions for patients. Objective To define the specific responsibilities of nurses in facilitating smoking cessation among patients, and provide guidance for future nursing interventions in smoking cessation. Methods The scoping review process was conducted for Arksey and O'Malley's framework. Based on the three-step search strategy of Joanna Briggs Institute (JBI), a comprehensive search was performed across ten databases including PubMed, CINAHL, Web of Science, Embase, Cochrane Library, OVID, PsycINFO, CNKI, Wan Fang Data Knowledge Service Platform, and VIP Database for Chinese Technical Periodicals, covering studies from the inception of the databases to February 2024. The inclusion and exclusion criteria were developed using the JBI (participants, content, and context) principle. Randomized controlled trials or quasi-experimental studies with nurse-led or involved smoking cessation interventions for patients were included. Data extraction was conducted independently by two reviewers. The findings were reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR). Results In total, 53 studies were eligible for the final charting and synthesis. The analysis identified six key roles that nurses played in smoking cessation interventions: assessors, educators, practice facilitators, coordinating collaborators, organizers, and supervisors. Among these, the roles of assessors, educators, and practice facilitators were the most commonly reported. The motivation interview and 5A method were the predominant techniques employed for smoking cessation. Nurses primarily promoted smoking cessation through the distribution of pamphlets, face-to-face education, and the provision of smoking cessation guidance. The primary participants in these studies were patients with chronic obstructive pulmonary disease (COPD). Conclusions Nurses play an indispensable role in smoking cessation interventions, occupying multiple critical roles. However, this review identified a gap in the pre-intervention training of nurses, indicating a need for enhanced training programs to better prepare nurses for effective smoking cessation interventions.